Developing a Socio-Ecological L-E-A-D Training Model for Green Skills and Circular Economy Agency - Herwina, Wiwin; Haidar, Muslim; Oktiwanti, Lesi; Syaiful, Rizal Fahmi; Syafitri, Elsa (Journal of Nonformal Education, 2026)
Background – Village waste banks can connect household waste separation with circular value creation, but participation, green competence, and continuity of community action often remain uneven.Research Urgency – Existing waste-bank activities frequently emphasize awareness or sorting practice without integrating local ecological diagnosis, adult learning, supervised application, and community agency in one coherent nonformal training sequence.Research Objectives – This study developed a socio-ecological L-E-A-D training model and examined preliminary short-term changes in green knowledge, green attitudes, green skills, and circular economy agency among adult community participants.Research Method – The study used three development phases: qualitative needs assessment, prototype development with expert review, and a pre-experimental one-group pretest-posttest field study involving 30 purposively recruited participants at the Mugarsari Waste Bank, Tasikmalaya. A 20-item measure covered four outcome domains. Validation indices must be completed from the original validation records before submission.Research Findings – The overall mean increased from 58.60 to 86.23. The recalculated normalized gain was 0.667. Based on the reported summary, the mean paired difference was 27.63 (SDdiff = 2.41), 95% CI [26.73, 28.53], t(29) = 62.70, p < .001, Cohen’s dz = 11.45. The unusually large statistic and effect size require verification against raw data or software output.Research Conclusion – The results indicate preliminary short-term within-group improvement after training, but they do not establish causal effectiveness because the study lacked a control group, long-term follow-up, and fully reported validation evidence.Research Novelty/Contribution – The study operationalizes socio-ecological andragogy as L-E-A-D: Local Ecology, Education, Action, and Development, connecting place-based problem mapping, participatory adult learning, supervised waste-management practice, and development of community agency.